Rarefied flow and heat transfer characteristics of rectangular cavities with heated concave surface - Ammar Alkhalidi (Advances in Mechanical Engineering, 2019)
This article utilizes the finite volume method to solve the problem incorporating rarefied flow and heat transfer characteristics inside concaved cavities. Cavities are used in many applications, one of which is building insulation to reduce heat loss from walls. In this article, the influence of the aspect ratio ( B / H ), the tilt angle ( θ ), Knudsen number ( Kn ), and Rayleigh number ( Ra ) on these characteristics were studied. Parameters ranges were 0 . 25 < B / H < 0 . 5 , 10 3 < Ra < 10 6 , 0 ° < θ < 90 ° and 0 ≤ Kn ≤ 0 . 1 . This study shows that the average Nusselt number ( Nu ) decreases as the B/H and Kn increase. Whereas, Nu increases with increasing Ra . In addition, the Nu increases as θ increases to a given critical angle (60°), and beyond this angle, Nu decreases with increasing Ra . A new correlation of Nu including all parameters investigated in this work is introduced. This study reveals that concaved cavities could be used as thermal insulation bodies.